Ask Question
23 October, 21:49

Simplify 3 - b (7b + 2) + 3b - (11 - b).

0
Answers (1)
  1. 23 October, 22:44
    0
    Simplifying 7b + - 4 + 3b + 11 + - 1b = 0

    Reorder the terms: - 4 + 11 + 7b + 3b + - 1b = 0

    Combine like terms: - 4 + 11 = 7 7 + 7b + 3b + - 1b = 0

    Combine like terms: 7b + 3b = 10b 7 + 10b + - 1b = 0

    Combine like terms: 10b + - 1b = 9b 7 + 9b = 0

    Solving 7 + 9b = 0

    Solving for variable 'b'.

    Move all terms containing b to the left, all other terms to the right.

    Add '-7' to each side of the equation.

    7 + - 7 + 9b = 0 + - 7

    Combine like terms: 7 + - 7 = 0 0 + 9b = 0 + - 7 9b = 0 + - 7

    Combine like terms: 0 + - 7 = - 7 9b = - 7

    Divide each side by '9'. b = - 0.7777777778 Simplifying b = - 0.7777777778
Know the Answer?
Not Sure About the Answer?
Find an answer to your question 👍 “Simplify 3 - b (7b + 2) + 3b - (11 - b). ...” in 📗 Mathematics if the answers seem to be not correct or there’s no answer. Try a smart search to find answers to similar questions.
Search for Other Answers